TINJAUAN HUKUM HOLDING COMPANY DALAM KAITANNYA DENGAN PERSEROAN TERBATAS - Chairan, A. Tenripadang (DIKTUM: Jurnal Syariah dan Hukum, 2010)
This article unearths holding hompany from legal perspective. This study finds out that the establishment of holding company gives some benefits that, in turn, upgrade the ethos of a company, i.e: (a) operational system is more efficient; (b) independent risk is negated; (c) the decision is more accurate so that the goals will be more efficiently reached. The responsibility of holding company to its sub-company is actually limited based on share. Nevertheless, as the contractual relationship is established, according to 1995 Limited Company Constitution, the responsibility can be extended.